2002
DOI: 10.2320/matertrans.43.2370
|View full text |Cite
|
Sign up to set email alerts
|

High Strain Rate Superplasticity in an Al-Li-Mg Alloy Subjected to Equal-Channel Angular Extrusion

Abstract: The superplastic behavior of an Al-4.1%Mg-2.0%Li-0.16%Sc-0.07%Zr alloy (1421 Al) subjected to intense plastic straining by equalchannel angular extrusion (ECAE) was studied in the temperature interval 250-450 • C at strain rates ranging from 1.4 × 10 −5 to 1.4 s −1 . The grain size after ECAE was about 0.8 µm and the fraction of high angle boundaries was about 80 pct. The highest elongation of 1850% without failure appeared at a temperature of 400 • C and initial strain rate of 1.4 × 10 −2 s −1 with correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 15 publications
(41 reference statements)
0
30
0
3
Order By: Relevance
“…It was shown previously [31] that ECAP at 300 • C of this alloy provides the formation of the well-defined subgrain structure (ε~2), partially recrystallized structure (ε~4) and fully recrystallized structure (ε~8). The last structure is uniform with an average grain size of~1 µm [2,[29][30][31]; most of the crystallites are true grains entirely outlined by HAGBs. This structure is essentially stable under annealing at a temperature of 450 • C [2,30,32].…”
Section: Ecap Processing Of Age Hardenable Aluminum Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown previously [31] that ECAP at 300 • C of this alloy provides the formation of the well-defined subgrain structure (ε~2), partially recrystallized structure (ε~4) and fully recrystallized structure (ε~8). The last structure is uniform with an average grain size of~1 µm [2,[29][30][31]; most of the crystallites are true grains entirely outlined by HAGBs. This structure is essentially stable under annealing at a temperature of 450 • C [2,30,32].…”
Section: Ecap Processing Of Age Hardenable Aluminum Alloysmentioning
confidence: 99%
“…The last structure is uniform with an average grain size of~1 µm [2,[29][30][31]; most of the crystallites are true grains entirely outlined by HAGBs. This structure is essentially stable under annealing at a temperature of 450 • C [2,30,32]. Therefore, this alloy can be subjected to solution treatment followed by quenching with a UFG structure.…”
Section: Ecap Processing Of Age Hardenable Aluminum Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown [6][7][8] that equal-channel angular extrusion (ECAE) is capable of producing a significant grain refinement in commercial scale rods of aluminum alloys due to occurrence of dynamic recrystallization during intense plastic straining by simple shear. Aluminum alloys subjected to ECAE with large strains could exhibit high superplastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…4) However, Primdahl et al 8) showed that such intergranular cracks might be also originated from the volume increase associated with the tetragonal to monoclinic transformation induced in some grains during grinding and polishing processes to a TEM foil. Despite a large number of studies concerning cavitation behaviors in superplastic materials, [3][4][5][6][7][8][10][11][12][13] only a few data -obtained from exactly as-deformed specimens, i.e., without the surface preparation -have been reported so far. It is probable that the surface preparation of specimens before the evaluation of cavitation may give errors in the data.…”
Section: Introductionmentioning
confidence: 99%